Carcinoma showing thymus like elements: Report of a case with EGFR T790M mutation. Issue 5 (8th November 2017) - Rajeshwari, Madhu; Singh, Varsha; Nambirajan, Aruna; Mridha, Asit Ranjan; Jain, Deepali
Abstract: Carcinoma showing thymus‐like differentiation of the thyroid (CASTLE) is a rare tumor involving the thyroid and perithyroidal soft tissues. It shares morphological, immunohistochemical and molecular similarities with thymic carcinomas. Due to its relatively better prognosis, it needs differentiation from other primary and metastatic tumors of this region. A 40‐year‐old lady presented with a gradually progressive anterior neck swelling for one year. Imaging showed bulky right and left lobes of thyroid along with a solid soft tissue mass in the pretracheal region. Fine needle aspiration smears showed features of poorly differentiated carcinoma. Total thyroidectomy with excision of the mass revealed histopathological features characteristic of CASTLE, with evidence of thyroiditis in adjoining thyroid. Epidermal growth factor receptor (EGFR) assay revealed presence of EGFR T790M somatic mutation in exon 20. The same was not detectable on direct sequencing. We present a rare case of CASTLE, occurring in association with Hashimoto thyroiditis, with emphasis on cytological features and report for the first time the presence of a low level somatic mutation in EGFR (EGFR T790M mutation).